PEMBAURAN AGAMA DAN STRATEGI POLITIK KEBUDAYAAN: Kontestasi Identitas Etnis dalam Narasi Masyarakat Multikultur - Mujib, Ibnu (El-HARAKAH (TERAKREDITASI), 2009)
As a strategy of the political culture, religious assimilation constructed in New Order has become a concept which is considered uneffective and failure. The Post-reformation era has become the sign of the failure of the concept of religous assimilation. The policy of the religious assimilation which is disigned for reducing conflicts between âPribumi vs Tionghoaâ. In fact, it has sharpenned and deepened the gaps between the two groups. Religious conversion by the Chiness in terms of assimilationism of new order turns to be a political strategy to describe and to have the pribumi identity which is considered as the majority and muslim. In this case, everyone can claim their own identity and say âwho I amâ, âwho you areâ, and âwho we areâ. In the future, for the agenda of assimilation, religious conversion will loose itâs the relevance. It is see that the process of assimilation appears from social engeneering that separates the differences of cultural roots of âTionghoa-Pribumiâ while the contestation of culture in area of multiculturalism reunites the entity of diversity into the singgel identity. Therefore, the celebration of Chines New Year (IMLEK) in mosques in Yogyakarta becomes a form of integration of identity between Tionghoa-Islam and Java.Â Â Â Â